2010
DOI: 10.1017/s1474748010000034
|View full text |Cite
|
Sign up to set email alerts
|

Twisted geometric Satake equivalence

Abstract: Let k be an algebraically closed field andFor an almost simple algebraic group G we classify central extensions 1 → Gm → E → G(F ) → 1; any such extension splits canonically over G (O). Fix a positive integer N and a primitive character ζ : µ N (k) →Q * (under some assumption on the characteristic of k). Consider the category of G(O)-bi-invariant perverse sheaves on E with Gm-monodromy ζ. We show that this is a tensor category, which is tensor equivalent to the category of representations of a reductive groupǦ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(60 citation statements)
references
References 8 publications
2
53
0
5
Order By: Relevance
“…To the covering group G (n) , one may associate a complex dual group which may be distinct from the dual of G (see [36], [17], and [40]). Let B Q : Y × Y → Z be the symmetric bilinear form associated to the quadratic form Q.…”
Section: Brylinski-deligne Extensionsmentioning
confidence: 99%
“…To the covering group G (n) , one may associate a complex dual group which may be distinct from the dual of G (see [36], [17], and [40]). Let B Q : Y × Y → Z be the symmetric bilinear form associated to the quadratic form Q.…”
Section: Brylinski-deligne Extensionsmentioning
confidence: 99%
“…A morphism from a collection { 1 L µ n } to another collection { 2 L µ n } is a collection of maps 1 L µ n → 2 L µ n in Perv ζ (X µ n ) compatible with the isomorphisms (21). Let j poles :Ẋ n ֒→ X n be the complement to all the diagonals.…”
Section: The Fs Categorymentioning
confidence: 99%
“…We fix the following data as in ( [32], Section 2.3). Write Gr G = G(F )/G(O) for the affine grassmannian of G. For j ∈ J let L j denote the (Z/2Zgraded purely of parity zero) line bundle on Gr G with fibre det(g j (O) : g j (O) g ) at gG(O) (the definition of this relative determinant is found in [21]). Let E a j be the punctured total space of the pull-back of L j to G(F ).…”
mentioning
confidence: 99%
“…B.y 1 ; y 2 / D Q.y 1 C y 2 / .Q.y 1 / C Q.y 2 //: Recently, a number of authors [7,24,26] have found a "dual group" to a metaplectic group, or at least the root datum thereof. The combinatorics of this construction are below.…”
Section: Cartan Datamentioning
confidence: 99%